TECHNOLOGY OF TEACHING ENGLISH IN HIGH SCHOOLS - Xаlikоvа Latofat (Журнал иностранных языков и лингвистики, 2023)
This article describes the technology of language teaching in English classes in secondary schools in the Namangan region, which aims to create such an environment for students not only during class activities but also in the breaks between classes to successfully master English language skills